Superworm (Zophobas morio) Cooking Oil Production Process (Study On NaOH And Bentonite Concentration) - -, Mush'ab - (Journal of Food and Life Sciences, 2018)
ABSTRACTDarkling beetle larvae or superworm (Zophobas morio) has the potential as an environmentally friendly cooking oil. Superworm contains 80% fatty acid and high productivity. Increasing the quality of superworm cooking oil is done by neutralizing alkali using NaOH and bleaching using bentonite. The aim of this research is to know the effect of the corresponding concentration of NaOH and bentonite on superworm cooking oil. The research method used Factorial Random Block Design with 2 factors, ie NaOH concentration (16 oBe, 18 oBe, and 20 oBe) and bentonite (1.2% w/w, 1.4% w/w and 1.6% w/w). The results showed that the interaction between the two factors that is the concentration of NaOH and bentonite give significant influence to the value of free fatty acid and water content of superworm cooking oil. The value of free fatty acid content fulfills the standard of cooking oil fatty acid (SNI 3741: 2013) maximum of 0.6 mg KOH/g, while the water content value is only few that meet the cooking oil content standard (SNI 3741: 2013) maximum 0,15% w/w. The best treatment result was obtained at N3B3 treatment (20 oBe concentration of NaOH and 1.6% w/w bentonite) to superworm cooking oil with free fatty acid content and moisture content of 0.235 mg KOH/g and 0.047% w/w.Â Keywords: Bleaching, Cooking oil, Neutralization, Superworm